PEKERJAAN IBU MEMPENGARUHI PEMBERIAN MPASI DINI BAYI 0 - 6 BULAN - Nugraheni, Diah Eka (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Early complementary feeding in Bengkulu is still highbased on data obtainedfrom Bengkulu Profile Provinsi in 2012 the total of babies who are exclusively breastfedbabies 417 803 (41%) of the 43 953, meaning there is 26.015 infants (51%) were gets anearlycomplementary feeding. The problem of this study is the high incidence of givingextra food for baby before the baby is 6 months old. The purpose ofthis research was todetermine the factor sassociated with Early complementary feeding in Sawah lebar KotaBengkulu. Types of research is descriptive analytic method with the cross sectional studydesign. The population is mothers with infants aged 0-6 months which amounted to 279babies. Samples were taken by using a Acciedental sampling technique as many as 164babies. The results showed, work have p value=0.009 with OR2.48, This indicates that thevariable, work has p value<0.05 means significant relationship with the provision of earlycomplementary feeding. Health workers are expected to conduct health educationregarding appropriate supplemental feeding on the baby's mother.